6 - The Status of Yorùbâ Dialects in Communicative Competence and Language Proficiency: DOI: 10.4314/ad.v29i3.22202 - Fabùnmi , Felix Abidèmi (Africa Development, 2004)
This paper attempts to explore the status of Yorùbâ dialects in communicative competence and language proficiency. Dialectal identities are quite strong among the Yorùbâ people; they form an integral part of sociolinguistic behaviour in any of the Yorùbâ communities. So, during speech acts or communication, the centralised version of the language will invariably depict the native speaker's version as deviating from the so-called standardised rules of speaking. But such dialectal identities and expressions actually mirror the people's mind, most covertly when deciding the topics that are appropriate to a particular speech event. This is the essence of communicative competence. It is however discovered in this paper that such proficiency could not be enhanced among the Yorùbâ people unless skilled dialectal knowledge is allowed to thrive. The Yorùbâ people appear to have rather strong views on the appropriateness of their dialects in different situations. The work is conceptualised within the framework of Chomsky's 'states' of mind where the adult native speaker's knowledge is fully developed static competence. Our corpora are largely taken from various dialectal renditions and written texts. Oral and structured interviews were also conducted among Yorùbâ language students and among Yoruba native speakers. This was decided in order to reduce introspection in diverse forms.